Valorization of diverse sizes of coal bottom ash as fine aggregate in the performance of lightweight foamed concrete - Haddadian, Arian; Alengaram, U. Johnson; Alnahhal, Ahmed Mahmoud; Salari, Farhang; Srinivas M, Karthick; Mo, Kim Hung; Yusoff, Sumiani; Ibrahim, Muhammad Shazril Idris (Journal of Civil Engineering and Management, 2022)
In recent years, research work on the use of coal bottom ash (CBA) as a partial alternative for aggregate in concrete is on the rise. This research is aimed at examining the characteristics of lightweight foamed concrete with CBA as fine aggregate to produce environmentally sustainable product. With the volume replacement technique, CBA was used as 25%, 50%, 75%, and 100% replacement for conventional mining sand with different sieve sizes of smaller than 4.75, 2.36, and 0.6 mm in concrete. Water absorption, porosity as well as mechanical characteristics tests, including compressive strength, splitting tensile strength, and modulus of elasticity (MOE) were conducted and analyzed. X-ray diffraction and scanning electron microscopy microstructural investigations were also performed to correlate test results. The quality of concrete was investigated using a non-destructive ultrasonic pulse velocity test. According to the findings, the highest replacement level of CBA with a sieve size smaller than 0.6 mm had an impact in reducing workability. The effect of CBA particles on water absorption, MOE, compressive strength, and tensile strength depends on the size of the fine aggregate, the replacement ratio and the density. In general, substituting mining sand with CBA aggregate improved the mechanical performance of concrete, notably for the aggregate size of less than 0.6 mm. Moreover, the SEM images indicate that the addition of CBA particles decreased the size and quantity of voids in the foamed concrete.